Analysis of Recruitment and Selection Quality Improvement on The Indonesian National Armed Forces Personnel: A Case Study of The Garuda Task Force in MINUSCA - Angga Wijaya; Reza Fathurrahman (UIN Sunan Gunung Djati, 2022)
Peacekeeping-related research has increased in the last two decades as the number and complexity of peacekeeping operations, and the associated resource commitments have increased. However, studies investigating recruitment and selection issue remains understudied. Indonesia is known as a contributing country that deploys uniformed personnel as peacekeepers and serves under the banner of the United Nations. Efforts to ensure competent peacekeeping forces can be carried out through an objective recruitment and selection process. By reviewing the literature, this article aims to analyze the improvement of the quality of recruitment and selection of the personnel of the GarudaÂ Task Force, particularly the Multidimensional Integrated Stabilization Mission in the Central African Republic (MINUSCA). The results show the need to improve the quality of recruitment and selection of TNI personnel starting from the planning stage, vacancy announcement, to the selection stage, which consists of potential screening candidates, and selection interviews. In order to improve the recruitment and selection process, it is necessary to pay attention to the key factors both from the perspective of the employer and the candidate.